2007
DOI: 10.3923/pjbs.2007.1301.1304
|View full text |Cite
|
Sign up to set email alerts
|

The Growth of Tribolium castaneum (Herbst) and Lasioderma serricorne (Fabricius) on Feed Media Dosed with Flavour Volatiles Found in Dry Cocoa Beans

Abstract: Acetophenone, ethyl butyrate and 2-phenyl ethanol were used as additives to media on which Tribolium castaneum (Herbst) and Lasioderma serricorne (Fabricius) were cultured for 65 days. Acetophenone and ethyl butyrate had a positive impact on the weight and multiplication of the insects. The weight and rate of multiplication was higher in feed media containing acetophenone alone. The amount of the flavour volatiles added was high enough to deter the Lasioderma from feeding well, which affected their growth. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Even if the compounds responsible for the characteristic aroma of cocoa have been widely studied over the past century, these compounds are still of interest in view of various papers and studies published more recently . The compounds that give cocoa and chocolate their flavors are molecules such as pyrazines, aldehydes (cocoa aroma, nut), esters (fruity aroma), and phenolic compounds (astringent property).…”
Section: Introductionmentioning
confidence: 99%
“…Even if the compounds responsible for the characteristic aroma of cocoa have been widely studied over the past century, these compounds are still of interest in view of various papers and studies published more recently . The compounds that give cocoa and chocolate their flavors are molecules such as pyrazines, aldehydes (cocoa aroma, nut), esters (fruity aroma), and phenolic compounds (astringent property).…”
Section: Introductionmentioning
confidence: 99%
“…Jonfia-Essien et al . 36 , 37 found that acetophenone had a positive effect on the growth and development of red flour beetle ( Tribolium castaneum Herbst) and cigarette beetle ( Lasioderma serricorne Fabricius), and it was also an active substance stimulating antennae of red flour beetle. Jeanbourquin and Guerin 20 reported that EAG response of stable fly to acetophenone from equine feces was stronger than that from cattle feces, in which low levels of acetophenone were detected.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, these aggressive tree-killing bark beetles can rapidly colonize their host by producing an aggregation pheromone, which can be regulated by acetophenone-based multicomponent blends. It is interesting to note that other pest beetles are addicted to acetophenone, which had a positive impact on the weight and multiplication of the red flour beetle ( Tribolium castaneum ), a worldwide pest of stored products, and the tobacco beetle ( Lasioderma serricorne ), one of the most widespread and damaging pests for the tobacco industry, when they were treated with acetophenone-containing cultures that deter the beetles from feeding well, which affected their growth, and thus, acetophenone exhibits antifeedant properties in this case [ 47 ]. Acetophenone is also involved in complex interactions between fungal symbionts of the ambrosia beetle Platypus cylindrus and the cork oak ( Quercus suber ), an interesting plant that is the primary source of cork for wine bottle stoppers.…”
Section: Acetophenone Is a Prolific Semiochemical For Plant-feeding I...mentioning
confidence: 99%